Project MBO (Mastery of Basic Operations) In Improving the Numeracy Level of the K-3 Elementary Learners - Bauyon, Ma. Christina (JPAIR Multidisciplinary Research, 2023)
The Department of Education prioritizes improving literacy and numeracy in early learners, according to a joint research center funded by the Australian government and tasked with advising the government on improving the basic education system amid a pandemic. The rationale of the study is to improve the academic performance of the Key Stage 1 learners, encourage them to strive for excellence, and help them appreciate the application of different mathematical concepts in real-life situations. Furthermore, this integration of a new pedagogical approach reinforces the implementation of interactive approaches in classroom mathematics and other learning areas so learners’ performance in mathematics will increase and improve to above mastery level. The study used a descriptive quantitative design. Instruments such as the EGMA tool and teachers’ self-made supplementary material were employed to assess the efficacy of the inquiry-based learning strategy as measured by the mathematical achievement of K-3 Learners. The data showed significant differences between the learners’ performance before and after Project MBO implementation through the different interventions of the K-3 teachers, such as the validated instructional materials and interactive lessons. Based on the findings of the study, a compendium plan served as the output of the study.